2016
DOI: 10.15255/cabeq.2014.2148
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Studies Dedicated to the Development of a Novel Injectable Polymeric Blend for Viscosupplementation Treatment

Abstract: Viscosupplementation is an intra-articular symptomatic treatment of mild osteoarthritis. The treatment involves the injection of high-molecular-weight hyaluronan (HA), and especially of cross-linked HA to restore the lubricating and cushioning properties of the synovial fluid.This work involves the development of a novel viscosupplementation fluid based on amidated carboxymethylcellulose and obtained by blending the soluble polymer with its crosslinked derivative. Rheological analyses carried out under both os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…The rheological characterization of the HCC formulation (Figure 2) indicated a typical entangled network resembling those reported for healthy synovial fluid. The zero-shear viscosity and the dynamic moduli values are in agreement with the widely used HA-based intra-articular medical devices, thus predicting an appropriate response to stress conditions when injected [35–39]. Beside the viscoelastic properties, another crucial requirement is the injectability through fine bore needles to reduce pain during delivery [40].…”
Section: Discussionmentioning
confidence: 61%
“…The rheological characterization of the HCC formulation (Figure 2) indicated a typical entangled network resembling those reported for healthy synovial fluid. The zero-shear viscosity and the dynamic moduli values are in agreement with the widely used HA-based intra-articular medical devices, thus predicting an appropriate response to stress conditions when injected [35–39]. Beside the viscoelastic properties, another crucial requirement is the injectability through fine bore needles to reduce pain during delivery [40].…”
Section: Discussionmentioning
confidence: 61%
“…Interestingly, studies with commercial viscosupplements also exhibit a large dispersion in results. The zero shear rate viscosity of commercial viscosupplements can vary between 0.5 and 190 Pa•s [34,35]. It can be assumed that these low viscosity HA solutions will not perform well in the recovery of the rheological properties of osteoarthritic synovial fluid after mixing with it.…”
Section: Rheology Of Hamentioning
confidence: 99%
“…Viscosupplementation, involving (repeated) intrarticular injection of hyaluronan-based formulations, currently represents the most employed, not invasive, symptomatic treatment of the disease [ 7 ]. The delivery of HA-based formulations into the joint is intended to restore the rheological properties of the synovial fluid, resulting in pain relief and improved joint mobility [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Furthermore, the biochemical effect of HA on chondrocytes and synoviocytes may permit at least a partial restoration of physiological function, towards a certain grade of repair [ 15 ] A huge number of HA-based products intended for intrarticular injections are available on the market.…”
Section: Introductionmentioning
confidence: 99%
“…The information included in the leaflets is incomplete and, in most cases, not supported by either in vitro or in vivo studies, and relevant differences among them are rarely reported [ 16 ]. Rheological properties are mainly analyzed to evaluate the viscosupplementation potential, and reports comparing the performance of diverse formulations are available [ 10 , 17 , 18 ]. Furthermore, in vitro or animal studies describe results related to the biological features of the preparations without referring those to the rheological properties of the gels/products [ 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%